2017
DOI: 10.3389/fnmol.2017.00229
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β1-42 (Aβ1-42) Induces the CDK2-Mediated Phosphorylation of Tau through the Activation of the mTORC1 Signaling Pathway While Promoting Neuronal Cell Death

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder, characterized by cognitive impairment and memory loss. Amyloid β1-42 (Aβ) and hyper-phosphorylation of microtubule-associated protein tau have been considered as major histological features in AD. However, the mechanism of how Aβ induces the hyper-phosphorylation of tau remains to be clarified. In the present study, we investigated the underlying cellular mechanisms of Aβ with regard to the cell cycle regulatory protein-mediated phosphorylation of tau i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 58 publications
1
42
0
Order By: Relevance
“…Conversely, parkin overexpression retarded the cyclin E accumulation in cultured neurons treated with excitotoxin, and protected the neurons from the kainate-induced excitotoxicity [182]. Cyclin E expression is also related to AD [183][184][185], for example, expression of cyclin E in the brain induced cell cycle activation and Cyclin D1, associated with CDK4 and CDK6, modulates the entry from quiescence (G 0 ) to the G1 phase of the cell cycle, and is also linked to the progression of neurodegeneration. Cyclin E plays a role in the initiation of DNA replication at the G1/S checkpoint, and also causes neurodegeneration in the postmitotic neurons.…”
Section: Cyclin Ementioning
confidence: 99%
“…Conversely, parkin overexpression retarded the cyclin E accumulation in cultured neurons treated with excitotoxin, and protected the neurons from the kainate-induced excitotoxicity [182]. Cyclin E expression is also related to AD [183][184][185], for example, expression of cyclin E in the brain induced cell cycle activation and Cyclin D1, associated with CDK4 and CDK6, modulates the entry from quiescence (G 0 ) to the G1 phase of the cell cycle, and is also linked to the progression of neurodegeneration. Cyclin E plays a role in the initiation of DNA replication at the G1/S checkpoint, and also causes neurodegeneration in the postmitotic neurons.…”
Section: Cyclin Ementioning
confidence: 99%
“…This possibility is supported by previous reports (Cicero and Herrup, 2005). In extension, Cdk5 overactivation, which is associated to neurodegenerative processes (Su and Tsai, 2011), is likely concomitant to the release Cyclin E. Hence, we suggest that pathophysiological events linked to neurotoxic Cdk5 activity can be alternatively or complementarily accounted by Cdk2 activation (Lee et al, 2017). In support, Cdk5 deregulation is associated to aberrant tau phosphorylation (Su and Tsai, 2011) and Cyclin E/Cdk2 can also phosphorylate tau (Schmetsdorf et al, 2009).…”
Section: The Ban On Neuronal Cell-divisionmentioning
confidence: 66%
“…25, 2018; 6 neurons, which was suggestive of neuronal death. This was not surprising, as Cyclin E is consistently associated to apoptosis during aberrant cell-cycle re-entry in neurons (Absalon et al, 2013;Copani et al, 1999;Lee et al, 2017;Schwartz et al, 2007;VeasPérez de Tudela et al, 2015;Verdaguer et al, 2002). Thus, we assessed if t1EK2 was inducing apoptosis by active caspase-3 immunolabeling.…”
Section: T1ek2 Induces Dna Synthesis and Apoptosis In Differentiated mentioning
confidence: 88%
See 1 more Smart Citation
“…Aberrant phosphorylation of tau protein can cause changes in synaptic structure and function, synaptic loss, and neurotransmitter inactivation [27] and induce learning and memory impairment and loss of synaptic function in transgenic model mice [28]. A recent report has shown that the Aβ polypeptide fragments were involved in promoting the high phosphorylation of tau protein through mTOR signaling pathway to induce nerve apoptosis [29], while some studies have shown that the p38 MAPK signaling pathway may also contribute to the regulation of tau protein phosphorylation in the hippocampus [30,31]. In our study, the neurons with high expression of P-p38 and P-tau were observed in the hippocampus CA1, CA3, and GD areas of SAMP8 mice.…”
Section: Discussionmentioning
confidence: 99%